Book Review – White Lotus Rebels and South China Pirates: Crisis and Reform in the Qing Empire - Wang , Gungwu (Penerbit Universiti Sains Malaysia (USM Press), 2014)
This book studies the Qianlong-Jiaqing transition (1796–1810), a relatively neglected period in modern Chinese history. It probes some key factors that led to the rise of High Qing in the 18th century and its subsequent decline in the 19th century. It is widely known that the Qianlong emperor, in his last years, was responsible in weakening his powerful empire, but there have been arguments on the extent to which his successor's careful and conservative reforms helped restore order to imperial governance. The author, Wang Wensheng goes further than previous studies in identifying not only the White Lotus Rebellions of 1796–1804 but also the South China pirate attacks of 1802–1810 as relevant events in understanding the limits of Jiaqing's reforms. He points to the desultory but not insignificant attempts by some of the leaders of both groups to link their respective anti-regime causes. Using the two sets of events, the author suggests that the end of this period was neither the beginning of a dynastic decay nor the lull before the storm. The study shows that Emperor Jiaqing, subtly and cautiously, did reorganise the administrative machinery and regain credibility for the Qing regime. The emperor also recognised that changes in the external environment brought about by British and French interests along China's maritime frontiers required adjustments to traditional ideas of inter-state relations.